2016
DOI: 10.1039/c6cp03307e
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling order and conductivity in doped conducting polymers

Abstract: Herein it is demonstrated that the high level of interchain ordering of pEDOT is not necessary for the polymer to have efficient charge transport. Resistance and order are compared during the manufacturing process, where the polymerisation step and ordering step are decoupled as separate stages of the processing. GIWAXS experiments measuring interchain order are correlated to resistivity measurements at multiple stages of the manufacturing process on single films, and it is shown that for an individual film, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…It was reported that rinsing the as-cast PEDOT films could cause a collapse and volume contraction of the film due to removal of residuals (Ouyang et al., 2018, Winther-Jensen et al., 2005). Owing to this, SSP PEDOT displays a more aggregated yet slightly rougher surface (Mayevsky et al., 2016).
Figure 4The Molecular Packing of SSP PEDOT(A and B) Atomic force microscopic height images of PH1000 and SSP PEDOT; the image size is 2 × 2 μm.(C) Particle size distribution of SSP PEDOT and PH1000.(D) XRD spectra of SSP PEDOT and PH1000.
…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that rinsing the as-cast PEDOT films could cause a collapse and volume contraction of the film due to removal of residuals (Ouyang et al., 2018, Winther-Jensen et al., 2005). Owing to this, SSP PEDOT displays a more aggregated yet slightly rougher surface (Mayevsky et al., 2016).
Figure 4The Molecular Packing of SSP PEDOT(A and B) Atomic force microscopic height images of PH1000 and SSP PEDOT; the image size is 2 × 2 μm.(C) Particle size distribution of SSP PEDOT and PH1000.(D) XRD spectra of SSP PEDOT and PH1000.
…”
Section: Resultsmentioning
confidence: 99%
“…There has been a claim that a high level of inter-chain ordering is not necessary for efficient charge transport of PEDOT because disordered PEDOT is as conductive as the ordered form as long as a sufficient number of charge carriers are present. 39,40 This implies that electron transport along the backbone of pdoped PEDOT, which would be less sensitive to inter-chain ordering, is as important as (or more important than) electron transport across π-stacked backbones. 29 Density functional theory (DFT) calculations on pristine and doped PEDOT crystals have also shown that the intra-chain transport is significantly faster than the inter-chain transport.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism is not completely clear. There has been a claim that a high level of inter-chain ordering is not necessary for efficient charge transport of PEDOT because disordered PEDOT is as conductive as the ordered form as long as a sufficient number of charge carriers are present. , This implies that electron transport along the backbone of p -doped PEDOT, which would be less sensitive to inter-chain ordering, is as important as (or more important than) electron transport across π-stacked backbones . Density functional theory (DFT) calculations on pristine and doped PEDOT crystals have also shown that the intra-chain transport is significantly faster than the inter-chain transport. ,,, In this case, another important factor to increase the conductivity would be the p -doping density of PEDOT, which would in turn depend on the power and the concentration of dopants as well as the interaction between the p -doped PEDOT and the anions staying near it to keep the charge neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…Only 6:4 blended films with both EISA conditions showed clear scattering spot at 0.44 Å −1 along the out-of-plane direction while 4:6 blended films did not show such a peak, as can be seen in inset images of Figure 3a−d. The ring patterns were attributed to residual iron tosylate and PEO crystals, 13 but the out-of-plane spot of the 6:4 blended films are oriented from the highly aligned PEDOT:Tos crystallite. 12 The spot is 14.3 Å of periodicity and correspondence with (100) peak from orthorhombic crystal structures of PEDOT:Tos which direction in a unit cell is coincident with elongated EDOT monomer direction and perpendicular against polymer backbone.…”
mentioning
confidence: 99%